2005
DOI: 10.1002/cncr.21047
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting bone mineral density in patients with prostate carcinoma before and after orchidectomy

Abstract: BACKGROUNDOrchidectomy is an accepted form of androgen‐deprivation therapy (ADT) for prostate carcinoma. Osteoporosis is common in elderly individuals and is accelerated by ADT. The authors studied changes in bone mineral density (BMD) after ADT and factors that affected those changes.METHODSFifty patients with prostatic adenocarcinoma who opted to undergo orchidectomy were studied prospectively. All patients completed 6 months of follow‐up, and 20 of those patients completed 12 months of follow‐up. Patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 59 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…At 6 months, the average BMD at lumbar spine decreased by 1.09% in treated population, which is not statistically significant. This fall of average BMD at lumbar vertebra by 1.09% at 6 months is much lower as compared to 12% fall in a similar population of untreated patients at the same site at 6 months as reported by Mayank et al 18 The incidence of side effects with once weekly alendronate is low and gastrointestinal side effects are comparable with that of placebo. 25 In our study one patient complained of upper gastrointestinal discomfort, which on subsequent evaluation was found to be due to gall stone disease.…”
Section: Changes In Average Bmdmentioning
confidence: 40%
See 1 more Smart Citation
“…At 6 months, the average BMD at lumbar spine decreased by 1.09% in treated population, which is not statistically significant. This fall of average BMD at lumbar vertebra by 1.09% at 6 months is much lower as compared to 12% fall in a similar population of untreated patients at the same site at 6 months as reported by Mayank et al 18 The incidence of side effects with once weekly alendronate is low and gastrointestinal side effects are comparable with that of placebo. 25 In our study one patient complained of upper gastrointestinal discomfort, which on subsequent evaluation was found to be due to gall stone disease.…”
Section: Changes In Average Bmdmentioning
confidence: 40%
“…Osteopenia or osteoporosis develops progressively 13 in a number of patients and can be a cause of significant mortality, 17 primarily because of incidence of hip fractures. In an Indian study, Mayank et al 18 reported 12% and 18% bone loss at 6 and 12 months respectively after orchidectomy.…”
Section: Changes In Average Bmdmentioning
confidence: 99%
“…1,10,[12][13][14][15][16] The three risk factors that have been reliably identified in patients with locally advanced disease are older age, low body mass index and a long duration of ADT. In metastatic prostate cancer, the only reliable risk factor is elevated levels of deoxypyridinoline.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The authors estimate that over 3000 fractures per year can be attributed to the use of ADT. Just as alarming are recent data that showed that patients begin having effects on BMD with LHRH agonist use in as little as 9 months of therapy and as quickly as 6 months after orchiectomy [35]. It seems that the majority of the bone loss occurs within the first year and then continues at a slower pace.…”
Section: Osteoporosismentioning
confidence: 99%